Let's Watch Live Streaming: How Streamer Credibility Influences Brand Attitude in Esports Streamer Marketing. (April 2022) - Xu, Qingru; Kim, Hanyoung; Billings, Andrew C.
This study explores if and how perceived Esports streamer credibility influences the audience's attitude toward the brand endorsed by the streamer. Results from a survey conducted with US adults ( N = 277) show the significant and positive relationship between streamer credibility and brand attitude while identifying parasocial relationships and streamer loyalty as two factors mediating the impact of streamer credibility on brand attitude. Structural equation modeling analysis is used to reveal how perceived expertise and trustworthiness of an Esports streamer affect viewer attitudes toward the promoted brands, with theoretical and practical implications outlined.